Association of self-reported cognitive concerns with mobility in people with lower limb loss. Issue 1 (2nd January 2018) - Kelly, Valerie E.; Morgan, Sara J.; Amtmann, Dagmar; Salem, Rana; Hafner, Brian J.
Abstract: Purpose: This study tested the hypothesis that greater perceived cognitive concerns are associated with worse mobility in a cohort of prosthesis users with lower limb loss (LLL). Method: We performed a secondary analysis of cross-sectional self-report data from a volunteer sample of people with LLL due to dysvascular and non-dysvacular causes. Perceived cognitive difficulties were assessed using the Quality of Life in Neurological Disorders Applied Cognition – General Concerns (Neuro-QoL ACGC). Mobility was measured with the Activities-Specific Balance Confidence Scale (ABC) and the Prosthetic Limb Users Survey of Mobility (PLUS-M). Simple linear regressions examined univariate relationships between cognitive concerns and mobility. Multiple linear regression analyses included demographic and amputation-related variables that could influence this relationship. Results: Analysis of data from 1291 people with LLL demonstrated that greater cognitive concerns, measured by the Neuro-QoL ACGC, were associated with poorer perceived mobility, measured by both ABC and PLUS-M instruments. This relationship remained statistically significant after adjusting for demographic and amputation-related factors. Conclusions: These results suggest that greater cognitive concerns are associated with worse mobility among a broad range of people with LLL. An improved understanding of this relationship is critical for optimizing rehabilitation outcomes for this population. Implications for rehabilitation: Rehabilitation for people with lower limb loss (LLL) typically focuses on physical impairments and mobility limitations, but cognition is increasingly recognized to have an impact on functional outcomes. Greater perceived cognitive concerns are associated with poorer mobility among a broad range of people with LLL, even when adjusting for demographic and amputation-related factors. Cognitive status can impact relevant rehabilitative outcomes, including mobility, and should be considered when planning prosthetic and therapeutic interventions.